Service quality in planned preventive maintenance: a preliminary study at UiTM campuses - Syamsul Anuar Mohd Dahari; Adi Irfan Che An; Afifuddin Husairi Mat Jusoh@Hussain; Suhana Johara; Anies Faziehan Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2024)
Planned Preventive Maintenance (PPM) is an essential component under facilities management (FM) carried out to ensure the functionality, effectiveness, reliability and safety of the asset and facilities. Poor service quality, lack of monitoring and performance assessment, low level customer satisfaction are among issues arises and has gained a lot of attention, especially among interested parties. In Universiti Teknologi Mara (UiTM) campuses context, FM normally outsourced to third parties namely concessionaires under Private Finance Initiative (PFI) campuses and contractors for conventional campuses. The main objective of this preliminary study was to investigate current practices in terms of service quality aspect of PPM works delivered by concessionaires and contractors in UiTM. A questionnaire was distributed to 27 respondents consist of 12 engineers and 15 assistant engineers from Office of Facilities Management UiTM and analysed using descriptive analysis. Based on the results, current practice to measure PPM work performance is by the number of works completed. Apart from that, there is no defined standard method available to be used as performance measurement in the aspect of service quality of PPM works delivered by concessionaires and contractors in UiTM. In addition, all the respondents agreed that there is indeed a necessity to develop a standard performance measurement in the aspect of service quality of PPM works delivered by concessionaires and contractors. The impact of this finding is to the Office of Facilities Management UiTM, in which they can focus and start to develop standard performance measurement in the aspect of service quality of PPM works delivered by concessionaires and contractors, so the services provided commensurate with the payment made and satisfy customer needs.